Identificación de competencias profesionales de psicólogos requeridas para su inserción laboral en los ámbitos clínicos, empresarial, y educativo, en el Ecuador en el año 2013-2014 - Medina Aguilar, Karla Medina (2014)
The degree to work it through developing data acquisition, through graduation program for graduates offered by the Technical University of Loja, in their mode of distance learning degree in psychology. The main objective of this research is to identify the competencies needed professional psychologists required alternate, clinical, business, and education. This study was conducted in 1,013 institutions: 290 mental health institutions, business 294, 284 and 145 educational alternative; through the Instrument diagnostic skills required by the institutions for psychologists. All skills evaluated were chosen by the institutions as essential that psychologists possess to perform their duties professionally. Institutions also saying that it is relevant to have a professional in psychology. Similarly labor niches identified for graduates are quite broad, psychologists can exercise their duties with greater openness in educational and mental health institutions; while the alternative institutions and organizational access is limited.